Reconceptualizing museum decolonization: A proposal for the repatriation of agency [version 1; peer review: 2 approved, 1 approved with reservations] - Francesca Bacci (Routledge Open Research)
This paper discusses how cultural governance leadership can adopt a decolonizing operational model for museums, to the advantage of all stakeholders. Key to the proposed framework is foregrounding the repatriation of ex-colonies’ agency as preparatory to the possible repatriation of their objects. The model hypothesizes the creation of an international alliance of museums, ministries of culture and universities/research institutes to form an accrediting body that certifies the status of “decolonized museum”, with appointed national curators or community representatives from each former colony. These professionals can be temporarily hired by institutions worldwide, to support the writing, displaying and storytelling revisions necessary to achieve the accreditation.